Successful Propranolol Treatment of a Kaposiform Hemangioendothelioma Apparently Resistant to Propranolol. Issue 7 (21st April 2016) - Filippi, Luca; Tamburini, Angela; Berti, Elettra; Perrone, Anna; Defilippi, Claudio; Favre, Claudio; Calvani, Maura; Della Bona, Maria Luisa; la Marca, Giancarlo; Donzelli, Gianpaolo
Abstract : A newborn with unresectable kaposiform hemangioendothelioma associated with Kasabach Merritt phenomenon, unresponsive to vincristine and prednisone, received second‐line treatment with propranolol at a dose of 2 mg/kg/day, starting at 2 months of life and continued for 13 months. There was only slight reduction in tumor mass, but measurement of propranolol levels showed extremely low plasma concentrations. The propranolol dose was progressively increased to 3.5 mg/kg/day, leading to a substantial increase in plasma levels associated with clinically relevant tumor reduction. This case highlights the importance of relating propranolol dose to its plasma concentration before considering the treatment ineffective for this vascular tumor.